Evaluasi Pengaruh Ekonomi Pembangunan Program Pemerintah dalam Peningkatan Akses Pendidikan dan Penciptaan Lapangan Kerja - Aditia Saputra; M. Fathir Farhat; M. Hasbi Ansyari; Fittrah Mirza (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This study encourages the influence of government programs in increasing access to education and job creation in Indonesia during the period 2019 to 2023. Using a mixed method that includes quantitative and qualitative approaches, this study analyzes secondary data and conducts in-depth interviews to understand the social context and community experiences. The results show a significant increase in the number of schools and scholarship programs, which have contributed to increasing graduation rates and reducing dropout rates, especially among students from low-income families. However, challenges such as unequal access to education in remote areas and lack of adequate educational infrastructure still need to be addressed. In addition, there is a positive relationship between education levels and poverty reduction, indicating that better education can increase employment opportunities. Job training programs have also proven to be important in preparing an efficient workforce, but need to be adjusted to the needs of a dynamic labor market. This study emphasizes the need for continuous evaluation of education and job training policies to optimally achieve national development goals and provide real benefits to the wider community.